(untitled) (Fiep Bulletin - online, 2016)
Self-care can be defined as the fulfillment of tasks that people do for their own benefit in maintaining health and well-being. The aim of the article was to identify self-care practice among nursing/Unioeste undergraduates, in Foz do Iguaçu/PR. This is an exploratory cross-sectional study, whose population is made up of 188 nursing students, and data collection was conducted in the first half of 2012, after approval by the Ethics Committee/Unioeste. Data were collected by administering a questionnaire to 120 students who volunteered to participate in this survey. On the subject of self-care, 91 students (75.83%) mentioned physical exercise practice, but only 44 (36.66%) do exercise, and the same occurred to all of the other self-care measures mentioned. Most of them did not perform any preventive screenings. Although college students have enough knowledge to perform self-care, they do not take care of themselves. There is a dualism in the speech of aspiring professionals and what they actually experience.